2019
DOI: 10.1136/bcr-2018-226721
|View full text |Cite
|
Sign up to set email alerts
|

Arterioportal fistula after partial gastrectomy treated with coil embolisation

Abstract: Arterioportal fistulas are a rare complication of abdominal interventions. They can remain asymptomatic for a long time and manifest with symptoms of portal hypertension. We present the case of a 65-year-old man admitted to the emergency room with increasing fatigue and melena. He had a history of partial gastrectomy with Billroth II reconstruction 40 years earlier for peptic ulcer perforation. On physical examination, he was pale and presented a machinery-type murmur in the epigastric area. Blood tests reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…While the development of APFs immediately after trauma has been described, one case of intrahepatic APF was diagnosed 2.5 years after hepatic injury. A review of other reports also revealed that some described APFs becoming symptomatic soon after the causative event(s) 3,9) , while others suggested that APF could gradually exacerbate 2,6,11,12) . Reportedly, APFs have been diagnosed 18-20 years after the causative event 10,11) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the development of APFs immediately after trauma has been described, one case of intrahepatic APF was diagnosed 2.5 years after hepatic injury. A review of other reports also revealed that some described APFs becoming symptomatic soon after the causative event(s) 3,9) , while others suggested that APF could gradually exacerbate 2,6,11,12) . Reportedly, APFs have been diagnosed 18-20 years after the causative event 10,11) .…”
Section: Discussionmentioning
confidence: 99%
“…Arterio-portal fistula (APF) describes an abnormal communication between artery and portal vein 1) , which can arise due to hepatic injury 1,2) , ablation therapy for tumors 3,4) , liver biopsies 5) , and surgeries 6) in adults. Although the entity is well-known, its incidence is rare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…antitrypsin deficiency, 9 one case of IgG4-related multiple coronary aneurysms, 10 one with the tumor communicating with portal vein to form portal vein fistula. 11 Treatments employed included endovascular therapy (n = 28, 59.6%), open surgical treatment (n = 8, 17.0%), and laparoscopic surgery (n = 2, 4.3%). There was one case where the patient received open surgery for Type II endoleak and hemorrhage after coil embolization.…”
Section: Case Reportmentioning
confidence: 99%
“…Other clinical features included nausea, vomiting, hematemesis, tarry stools, abdominal dropsy, anemia, hemothorax, and posterior mediastinal hematoma. Among those cases, seven patients, accompanied by pancreatitis, had complicated symptoms, 3–7 one with Marfan syndrome 8 (there was another one with systemic connective tissue disease, undiagnosed), one with α‐1 antitrypsin deficiency, 9 one case of IgG4‐related multiple coronary aneurysms, 10 one with the tumor communicating with portal vein to form portal vein fistula 11 . Treatments employed included endovascular therapy ( n = 28, 59.6%), open surgical treatment ( n = 8, 17.0%), and laparoscopic surgery ( n = 2, 4.3%).…”
Section: Literature Reviewmentioning
confidence: 99%